The influence of human resources management practices, corporate cultures and tasks integration on the performance of acquiring companies in Malaysia / Syazliana Astrah Mohd Idris - Mohd Idris, Syazliana Astrah (Institute of Graduate Studies, UiTM, 2017)
Despite decades of research, the key factors for success in Mergers and Acquisitions (M&As) and the reasons why M&As often fail remain poorly understood. The major reasons identified for this low performance include unrealistic expectation, unskilled execution, and incompatible cultures. However, many companies involved have only been evaluated based on their compatibility regarding financial figures and technical aspects, lack of research focused on the people issues. Malaysia has been continuously become the highest ranking in M&A exercises for the years of 2004 to 2007 and ranks between 2nd to 3rd among the top acquirers in the world for the following seven years. Unfortunately, many of Malaysian acquiring companies faced decline in their sales growth for the first 3 to 7 years that shows their performance has not been impressive after M&A and impacted Malaysian economy. In view of this, there is a need to investigate the influence of human resource management (HRM) practices and corporate cultures integration, focusing on the improvement of company performance. The research aims to investigate the influence of HRM practices on the performance of acquiring companies in Malaysia by examining the mediating effects of corporate cultures and tasks integration between the link...